A de novo X;13 translocation with abnormal phenotype. Issue 5 (October 1986) - Hodgson, S V; Barber, J C; Dowie, A; Dubowitz, V
Abstract : We describe a female infant who presented with hypotonia and developmental delay. Her karyotype showed a de novo balanced translocation between the X chromosome and chromosome 13, with breakpoints at Xq13 and 13p11. The normal X was late replicating in all cells examined. The cause of this patient's abnormal phenotype is discussed.